Design of a translation resource allocation controller to manage cellular resource limitations*. Issue 1 (July 2017) - Darlington, Alexander P.S.; Kim, Juhyun; Jiménez, José I.; Bates, Declan G.
Abstract: Microorganisms are widely used in synthetic biology for applications which require the simultaneous expression of multiple genes. However, gene expression in these microbes is limited by the number of free ribosomes. This resource limitation can result in the emergence of hidden regulatory interactions between co-expressed genes, such as gene coupling, where for example the expression of one gene decreases as another increases. In synthetic biology, where circuits utilising multiple new genes may be introduced into microbes, such hidden interactions can have serious consequences, since resource competition can introduce coupling which in turn causes circuit performance degradation or even failure. Here, we propose a novel approach that allows the decoupling of genes in the presence of resource limitations by dynamically controlling the allocation of translational resources between the host and circuit genes. We develop a complete mechanistic model that captures the key resource limitations in the system, and show how this model may be approximated by a reduced model that can be used for the purposes of controller design. An optimal resource allocation controller which decouples circuit genes is designed and used to guide the design of an experimentally feasible controller. Simulation results verify the ability of the controller to effectively remove the regulatory interactions imposed by translational resource limitations.